Tinjauan Hukum Penerapan”Prinsip”Good Corporate ”Governance”dalam”Perusahaan - Adhiani, Fayza Dwi; Apriani, Rani (Jurnal Ilmiah Wahana Pendidikan, 2024)
Good corporate governance mapping is the key to a company's success in getting added value to target goals in the long term or short term. Mapping good corporate governance is a new idea that is currently developing in the business world. Corporate governance is governance that is usually used with the aim of managing the running of a company. This governance has a large and broad impact in determining the company's goals and in the company's efforts to achieve the desired targets. Another impact is on the performance of a company so that it runs more optimally. Therefore, it is mandatory for corporations to implement Good Corporate Governance. On the other hand, implementing Good Corporate Governance Principles does not only require professional or ethical encouragement but is also driven by existing regulations